1993
DOI: 10.1089/dna.1993.12.597
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Chicken Apolipoprotein A-I Gene 5′-Flanking Region

Abstract: Apolipoprotein A-I (apoA-I) is a major protein component of plasma high-density lipoprotein in all species studied, and plays an important role in cholesterol homeostasis. In an earlier study, we cloned and structurally characterized the chicken apoA-I gene. In this study, the 5'-flanking region of the chicken apoA-I gene was sequenced and functionally characterized. Sequence analysis of the 510-nucleotide 5' upstream region revealed the presence of TATA and CCAAT boxes. In addition, we identified binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Moreover, we show the presence of both an activating (DR l) and modulating (DR2) sequence in the same response element as an interesting feature of the transcriptional regulation of the HD gene. This phenomena is also observed in the regulation of the hApoAI gene [16] and the mCRBPI1 gene [12]. Recent findings show that COUP-TF is able to bind to the 2 first motifs of this response element [9].…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, we show the presence of both an activating (DR l) and modulating (DR2) sequence in the same response element as an interesting feature of the transcriptional regulation of the HD gene. This phenomena is also observed in the regulation of the hApoAI gene [16] and the mCRBPI1 gene [12]. Recent findings show that COUP-TF is able to bind to the 2 first motifs of this response element [9].…”
Section: Discussionmentioning
confidence: 81%
“…ApoAI is a lipid-binding protein that participates in the transport of cholesterol and other lipids in the plasma. It is a major protein component of plasma high-density lipoprotein in all species, and plays an important role in cholesterol homeostasis (Bhattacharyya et al, 1993). In our previous study (Wang et al, 2006), ApoAI were found to be DE in adipose tissue between broilers and layers.…”
Section: Discussionmentioning
confidence: 91%
“…Apolipoprotein A-I is a lipid-binding protein that participates in the reverse transport of cholesterol from tissues to the liver for excretion by promoting cholesterol efflux CHICKEN ADIPOSE TISSUE DIFFERENTIAL PROTEOMICS from tissues and by acting as a cofactor for the lecithin cholesterol acyltransferase (Mukhamedova et al, 2008). It is a major component of high-density lipoprotein and plays an important role in cholesterol dynamic balance (Bhattacharyya et al, 1993). Genetic deficiency in APOA-I is associated with excessive intracellular cholesterol accumulation in humans and poultry (Breslow, 1989;Kiss et al, 2001;Wang et al, 2006a).…”
Section: Proteomic Analysis Of Adipose Tissue Between Fat and Lean Brmentioning
confidence: 99%